THE COUNTRY IS RAPIDLY UNDERGOING URBANIZATION THROUGH SDG - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 11 January 2017 The Asia Leadership Conference (ALC) 2017 continued its programme with the Senior Leadership and Industry Player Roundtable Session at the USM Dewan Persidangan Universiti (DPU) attended by the USM Heads of Departments.